Political Liberalism in Canada: The Case of Syrian Refugees - Fahadayna, Adhi Cahya (Department of International Relations, Brawijaya University, 2019)
The refugee crisis in Canada has created political dynamics affected by the ideological spectrum in Canadian Politics. Liberalism is the most widely accepted political ideology among Canadians. Refugee and political liberalism have shared fundamental relations consdering political liberalism inextricable link with humanity as its core value. Admittedly, political liberalism requires a country or a government to fulfill its responsibility toward humanity by protecting or admitting refugees. Eventually, during the refugee crisis in Canada, political liberalism contributed a crucial role in the open-door policy toward refugees. Firstly, this paper will focus on the crucial attesting role of political liberalism toward the open-door policy of the Canadian government toward refugees. Secondly, this paper also focuses on measuring the extent to which political liberalism is widely accepted as a political ideology in Canada. Finally, the paper also seeks to discover the political justification of the open-door policy of Canada on the basis of political ideology. The paper draws on a literature study to explain the focuses of this paper.Key Words: Political liberalism, Canada, refugee crisis, and the open-door policy